2014
DOI: 10.1093/glycob/cwu124
|View full text |Cite
|
Sign up to set email alerts
|

Semi-rational approach for converting a GH36 α-glycosidase into an α-transglycosidase

Abstract: A large number of retaining glycosidases catalyze both hydrolysis and transglycosylation reactions. In order to use them as catalysts for oligosaccharide synthesis, the balance between these two competing reactions has to be shifted toward transglycosylation. We previously designed a semi-rational approach to convert the Thermus thermophilus β-glycosidases into transglycosidases by mutating highly conserved residues located around the -1 subsite. In an attempt to verify that this strategy could be a generic ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…However, such approaches require either in-depth structural and biochemical knowledge and, in some cases, use of sophisticated computational methods (rational design); or the creation of large libraries, introducing location-agnostic modifications, coupled with powerful phenotypic screens (random mutagenesis) 18 . Nevertheless, by simply targeting a small number of conserved active-site residues in several retaining GHs [19][20][21] , we previously demonstrated that transglycosylation capability can be improved without extensive screening using structural information coupled with sequence conservation analysis. Moreover, others have transposed our obtained beneficial mutations to related enzymes, leading to significant transglycosylation yields 22 .…”
mentioning
confidence: 99%
“…However, such approaches require either in-depth structural and biochemical knowledge and, in some cases, use of sophisticated computational methods (rational design); or the creation of large libraries, introducing location-agnostic modifications, coupled with powerful phenotypic screens (random mutagenesis) 18 . Nevertheless, by simply targeting a small number of conserved active-site residues in several retaining GHs [19][20][21] , we previously demonstrated that transglycosylation capability can be improved without extensive screening using structural information coupled with sequence conservation analysis. Moreover, others have transposed our obtained beneficial mutations to related enzymes, leading to significant transglycosylation yields 22 .…”
mentioning
confidence: 99%
“…Based on previous studies aimed at improving transglycosylation in rGHs, 14,16,17,[50][51][52][53][54] it is well-established that mutations that lower the hydrolytic component of the reaction and others that increase acceptor binding can lead to overall improvements in transglycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the key molecular determinants that differentiate TGs from hydrolytic GHs are still unclearly defined, despite considerable efforts to discover these and relevant studies on reversed transglycosylation/hydrolysis (T/H) partition. [12][13][14][15][16][17] The class of GHs (retaining GHs, hereafter referred to as rGHs) mostly holding the potential to perform transglycosylation reactions are those that catalyze the hydrolysis of glycosidic bonds through a double displacement mechanism that results in the retention (in the product) of the configuration of the anomeric carbon originally present in the donor substrate. The reaction trajectory of rGHs is characterized by the formation of a more or less transient glycosylated enzyme reaction intermediate that can be deglycosylated either by a water molecule (hydrolysis), or by another suitable acceptor moiety (transglycosylation), including sugars and alcohols ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Another generic approach to increase trans-glycosylation activity of CAZymes is the mutation of other conserved residues in the active site to structurally related residues (e.g., from Tyr to Phe), which was first described in 2014 for a GH1 β-glycosidase [143] and has been transferred to many other GH families since then [144][145][146]. Recently, six conserved positions were identified from an alignment of 585 GH20 sequences and their effect on the trans-glycosylation activity of BbhI was studied [102].…”
Section: Mutation Of Other Conserved Active Site Residuesmentioning
confidence: 99%